Perancangan Buku Pakaian Adat Madura Untuk Anak Usia 9-12 Tahun Melalui Media Ilustrasi - Pratiwi Setiyo Trimawarni; Ida Siti Herawati; Mahendra Wibawa (LPPM STIKI Malang, 2020)
Madura traditional clothing illustration book is intended for children at the age of 9-12 years old or school age grades 3-6. The children can think spontaneously make interaction with objects in the environment and learn. The designer design the media through an attractive illustration book to interest the children in reading and observing the visualization. The Design Model is taken from Sanyoto design model, which begins with the background of the problem, identification, data sources, data analysis, synthesis, design concepts, the design, prototype and final process. The designing of an illustration book is conducted by using the sketch process then applying in digital by using Adobe Photoshop CC software and corel draw packaged into a hardcover book in 17.5 cm x 17.5 cm dimension. In addition to the main media, the project is also designing the support media to promote illustrative books on Madura traditional clothing such as x-banner, key chain, t-shirt, tote bag, glass and fan. This illustration book has its supporting media to promote illustration books on Madura traditional clothing, such as x-banner, key chain, t-shirt, tote bag, glass, fans and stickers. The next designer is expected to be able to design similar project by using different media.